A Comparative Study of Pali Grammar Books Pali Vaiyakorn by Prince Vajirananavarorasa and Moon Noi Asai Moon Yai by Somdet Phra Vanarat (DIT) - Honghern, Phermpoon; Tansrisook, Assist.Prof.Dr.Sompornnuch (Journal of Dhamma for Life, 2023)
The research article aims to analyze the two Pali grammar books written in Thai, Balee Vaiyakorn by Prince Vajirananavarorasa and Moon Noi Asai Moon Yai by Sondet Phra Vanarat (Dit), in the aspect of consequence, contents, and explanation techniques, and to compare them comprehensively. It is found that the similarity of the books is the result of the authors following Mulakaccayana, the use of tables in noun declension and verb conjugation, and the examples of noun and verb. However, they are different in the main points, i.e., the sequence of the contents, the topic of sound system, and the reference of Mulakaccayana Sutra in declension, conjugation, and derivation. Balee Vaiyakorn follows Mulakaccayana sequence, beginning with sound system and pronunciation, which are not found in Mulakaccayana, and not referring to any Mulakaccayana Sutra. However, Moon Noi Asai Moon Yai follows Saddabindu, another Pali grammar book, for the benefit of fast translation after finishing noun and verb. Significant Mulakaccayana Sutras are referred below the tables. These differences lead to the conclusion that they are not the imitation to each other. In overview, Balee Vaiyakorn is more consistent than Moon Noi Asai Moon Yai in content, use of technical terms, Pali example, Thai translation, and explanation. This characterizes modern language textbooks.